Assessment of the motor and emotional skills as factors of social skills among preschoolers at the St. therese Kinder School in Carles, Iloilo. - Ferreria, Krhistine Hazel B.
This study sought to find out if the motor and emotional skills of preschool children were related to their social skills. Twenty-eight (28) preschool children aging from 3 to 6 years olds served as respondents of this study. The respondents were randomly selected. The research design used for the study was the correlational design. Spearman Rank Correlation Coefficient was utilized for the data analysis. Results showed that there was a significant relationship between motor and social skills of preschoolers. The result of their emotional skills was also significantly correlated with their social skills.